Environmental education: Jacuizinho / RS - know, diagnosis to preserve! - Fiuza, Marionara Nogueira (2016)
This study aimed to assess the environmental characteristics of the Municipality of Jacuizinho / RS, assessing young people's views of school age about the strengths and weaknesses of your municipality urging them and their teachers to leave in search of evaluate it, analyzing the activities at the local level, but with consequences that reflect globally. The procedure used was the bibliographical research and field surveys with objective questions were applied to primary and secondary level students in two schools, one located in rural areas and the other in urban areas, and questionnaire with descriptive questions the teachers of the respective schools, which are involved with EA, it sought to interactively know the environmental reality which teachers and students are entered. It was noted that educators have difficulties in the integration of environmental education, reported the need for qualification and integration of environmental education as a discipline included in the school curriculum. This being one of the difficulties according to teachers directly affects the development and applicability of this study. For it to occur there needs the participation of all; the qualification of educational methods and professionals involved, developing a joint effort focused on reality in which the student is entered so that from this knowledge they are able to analyze the consequences of actions without planning and irrational use of natural resources.